2023
DOI: 10.1002/hpja.809
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of practice‐focused resources to support the implementation of place‐based approaches

Bojana Klepac,
Sara Branch,
Laura McVey
et al.

Abstract: Issue AddressedThere is increasing interest across public health research, policy, and practice in place‐based approaches to improve health outcomes. Practice‐focused resources, such as grey literature, courses and websites, are utilised by practitioners to support the implementation of place‐based approaches.MethodsA detailed search of two search engines: Google and DuckDuckGo to identify free practice‐focused resources was conducted.ResultsForty‐one resources met inclusion criteria, including 26 publications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In our project, based on the annual number of unique visitors to the Wellness Bus (~1000) and the two-year recruitment period, 25% of Wellness Bus clients expressed an interest in participating and 20% attended at least one nutrition class. While this proportion of Wellness Bus clients appears promising, it is necessary for others performing this type of community research to more systematically address reach to allow for comparisons across studies [ 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our project, based on the annual number of unique visitors to the Wellness Bus (~1000) and the two-year recruitment period, 25% of Wellness Bus clients expressed an interest in participating and 20% attended at least one nutrition class. While this proportion of Wellness Bus clients appears promising, it is necessary for others performing this type of community research to more systematically address reach to allow for comparisons across studies [ 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Applying the RE-AIM Framework in intervention planning also focuses on place-based strategies that take interventions to the local settings where populations that experience health disparities reside [ 47 ]. Using a place-based approach has been proposed to promote health and prevent disease by (1) addressing barriers to access (e.g., travel, time, cost), (2) aligning with local priorities and leveraging local assets to deliver the intervention, and (3) fostering community collaboration and cohesion [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen growing interest in how institutions of higher education can better facilitate, and participate in, knowledge translation and exchange (KTE). Recently published review research has found, for example, that public health researchers are not incentivised by their institutions -nor by public policy -to engage in KTE (Klepac, et al, 2023). In tandem, opportunities for university professional staff to network, share knowledge and practices, and collaborate on projects seem to run in a curious parallel to academic research.…”
Section: Sector-wide Knowledge Translation and Exchangementioning
confidence: 99%